Corrigendum: Diatom transcriptional and physiological responses to changes in iron bioavailability across ocean provinces - Natalie R. Cohen; Kelsey A. Ellis; Robert H. Lampe; Heather McNair; Benjamin S. Twining; Maria T. Maldonado; Mark A. Brzezinski; Fedor I. Kuzminov; Kimberlee Thamatrakoln; Claire P. Till; Kenneth W. Bruland; William G. Sunda; et al. (Frontiers in Marine Science, 2025)

The Dawn of the BioGeoSCAPES Program: Ocean Metabolism and Nutrient Cycles on a Changing Planet - Mak Saito; Harriet Alexander; Heather Benway; Philip Boyd; Martha Gledhill; Elizabeth Kujawinski; Naomi Levine; Mairead Maheigan; Adrian Marchetti; Ingrid Obernosterer; Alyson Santoro; Dalin Shi; et al. (Oceanography, 2024)
Biogeochemical cycles constitute Earth’s life support system and distinguish our planet from others in this solar system. Microorganisms are the primary drivers of these cycles. Understanding the controls on marine microbial dynamics and how microbes will respond to environmental change is essential for building and assessing model-based forecasts and generating robust projections of climate change impacts on ocean productivity and biogeochemical cycles. An international community effort has been underway to create a global-scale marine microbial biogeochemistry research program to tackle gaps in this understanding. The BioGeoSCAPES: Ocean Metabolism and Nutrient Cycles on a Changing Planet program will identify and quantify how marine microbes adjust to a changing climate and assess the consequences for global biogeochemical cycles. This article summarizes the ongoing efforts to launch BioGeoSCAPES.

An Ocean of Particles Characterization of Particulate Trace Elements by the GEOTRACES Program - Benjamin Twining (Oceanography, 2024)
The GEOTRACES program has greatly expanded measurements of trace elements, which serve as key nutrients, harmful contaminants, and tracers of ocean processes and past conditions. Many elements tend to associate with particulate matter, and GEOTRACES has been particularly valuable for growing our understanding of this fraction. Focusing on the micronutrient iron as an example, GEOTRACES data demonstrate that the majority of iron in the ocean is particulate. Chemically labile particulate iron, likely available for biological use, is also often more abundant than dissolved forms, particularly near continents and in the deep sea. This highlights the need to consider the particulate fraction in conceptual and numeric ocean models. Direct comparisons of particle-sampling methods highlight both the abundance of small particles (

Ocean iron fertilization may amplify climate change pressures on marine animal biomass for limited climate benefit - Alessandro Tagliabue; Benjamin S. Twining; Nicolas Barrier; Olivier Maury; Manon Berger; Laurent Bopp (Global Change Biology, 2023)
Climate change scenarios suggest that large‐scale carbon dioxide removal (CDR) will be required to maintain global warming below 2°C, leading to renewed attention on ocean iron fertilization (OIF). Previous OIF modelling has found that while carbon export increases, nutrient transport to lower latitude ecosystems declines, resulting in a modest impact on atmospheric CO 2 . However, the interaction of these CDR responses with ongoing climate change is unknown. Here, we combine global ocean biogeochemistry and ecosystem models to show that, while stimulating carbon sequestration, OIF may amplify climate‐induced declines in tropical ocean productivity and ecosystem biomass under a high‐emission scenario, with very limited potential atmospheric CO 2 drawdown. The ‘biogeochemical fingerprint’ of climate change, that leads to depletion of upper ocean major nutrients due to upper ocean stratification, is reinforced by OIF due to greater major nutrient consumption. Our simulations show that reductions in upper trophic level animal biomass in tropical regions due to climate change would be exacerbated by OIF within ~20 years, especially in coastal exclusive economic zones (EEZs), with potential implications for fisheries that underpin the livelihoods and economies of coastal communities. Any fertilization‐based CDR should therefore consider its interaction with ongoing climate‐driven changes and the ensuing ecosystem impacts in national EEZs.

Characterization and Speciation of Marine Materials Using Synchrotron Probes: Guidelines for New Users - Rose Jones; Sarah Nicholas; Paul Northrup; Benjamin Bostick; Colleen Hoffman; Wen Hu; Phoebe Lam; Alessandra Leri; Brandy Toner; Benjamin Twining (Oceanography, 2022)
Synchrotron instruments are useful for marine studies because they make nondestructive measurements of chemical composition and speciation on small sample volumes and at low concentrations. Synchrotron beamtime is available without cost using a peer-reviewed proposal system. New users do not have to be synchrotron radiation experts to design a good experiment, but some guidance is needed to design and propose appropriate experiments. Here we present some of that guidance to encourage and increase access to synchrotron facilities for marine science. We provide advice and examples from experts on how to access these instruments, choose the optimal sample preparation, and avoid common pitfalls. We then present some examples of successful marine studies that use these techniques.

Efficient zinc/cobalt inter‐replacement in northeast Pacific diatoms and relationship to high surface dissolved Co : Zn ratios - Riss M. Kellogg; Matthew R. McIlvin; Jagruti Vedamati; Benjamin S. Twining; James W. Moffett; Adrian Marchetti; Dawn M. Moran; Mak A. Saito (Limnology and Oceanography, 2020)
The importance of zinc (Zn) as a nutrient and its ability to be substituted for by cobalt (Co) have been characterized in model marine diatoms. However, the extent to which this substitution capability is distributed among diatom taxa is unknown. Zn/Co metabolic substitution was assayed in four diatom species as measured by the effect of free ion concentrations of Zn 2+ and Co 2+ on specific growth rate. Analysis of growth responses found substitution of these metals can occur within the northwest Atlantic isolate Thalassiosira pseudonana CCMP1335, the northeast Atlantic isolate Phaeodactylum tricornutum CCMP632, and within the northeast Pacific isolates Pseudo‐nitzschia delicatissima UNC1205 and Thalassiosira sp. UNC1203. Metabolic substitution of Co in place of Zn in the Atlantic diatoms supports their growth in media lacking added Zn, but at the cost of reduced growth rates. In contrast, highly efficient Zn/Co substitution that supported growth even in media lacking added Zn was observed in the northeast Pacific diatoms. We also present new data from the northeast Pacific Line P transect that revealed dissolved Co and Zn ratios (dCo : dZn) as high as 3.52 : 1 at surface (0–100 m) depths. We posit that the enhanced ability of the NE Pacific diatoms to grow using Co is an adaptation to these high surface dCo : dZn ratios. Particulate metal data and single‐cell metal quotas also suggest a high Zn demand in diatoms that may be partially compensated for by Co.

Subtle biogeochemical regimes in the Indian Ocean revealed by spatial and diel frequency of Prochlorococcus haplotypes - Alyse A. Larkin; Catherine A. Garcia; Kimberly A. Ingoglia; Nathan S. Garcia; Steven E. Baer; Benjamin S. Twining; Michael W. Lomas; Adam C. Martiny (Limnology and Oceanography, 2020)
While the majority of studies use the environment to describe microbial populations, the high diversity of microbes can conversely be used as a resource to understand subtle environmental variability. Here, we used a high‐resolution spatial and temporal analysis of Prochlorococcus sp. in the Eastern Indian Ocean to determine whether ecotypes and microdiverse taxa can be used to identify fine‐scale biogeochemical regimes in this under‐studied region. A total of 246 DNA samples were collected every 4–6 h in April 2016 on GO‐SHIP cruise I09N, which transected gyre, equatorial, and monsoonal ecosystems between Western Australia and the Bay of Bengal. Using amplicon sequencing of the highly variable rpo C1 marker, we found that the region was largely dominated by the Prochlorococcus HL‐II clade. Conserved single nucleotide polymorphisms (SNPs) were used to identify four microdiverse haplotypes, or SNP‐delineated taxa, within the HL‐II clade of Prochlorococcus . The haplotypes showed regional patterns of relative gene count abundance that were significantly correlated with environmental conditions. Additionally, we used nonlinear least squares models to fit the sine wave function to our data and demonstrate that the haplotypes show distinct patterns in relative diel frequency, providing evidence that these microdiverse populations are ecologically and evolutionarily distinct. Overall, we show how the integration of a genomics data set into a biogeochemical framework can reveal a more nuanced understanding of a complex ocean basin.

Divergent gene expression among phytoplankton taxa in response to upwelling - Robert H. Lampe; Natalie R. Cohen; Kelsey A. Ellis; Kenneth W. Bruland; Maria T. Maldonado; Tawnya D. Peterson; Claire P. Till; Mark A. Brzezinski; Sibel Bargu; Kimberlee Thamatrakoln; Fedor I Kuzminov; Benjamin S. Twining; et al. (Environmental Microbiology, 2018)
Summary Frequent blooms of phytoplankton occur in coastal upwelling zones creating hotspots of biological productivity in the ocean. As cold, nutrient‐rich water is brought up to sunlit layers from depth, phytoplankton are also transported upwards to seed surface blooms that are often dominated by diatoms. The physiological response of phytoplankton to this process, commonly referred to as shift‐up, is characterized by increases in nitrate assimilation and rapid growth rates. To examine the molecular underpinnings behind this phenomenon, metatranscriptomics was applied to a simulated upwelling experiment using natural phytoplankton communities from the California Upwelling Zone. An increase in diatom growth following 5 days of incubation was attributed to the genera Chaetoceros and Pseudo‐nitzschia . Here, we show that certain bloom‐forming diatoms exhibit a distinct transcriptional response that coordinates shift‐up where diatoms exhibited the greatest transcriptional change following upwelling; however, comparison of co‐expressed genes exposed overrepresentation of distinct sets within each of the dominant phytoplankton groups. The analysis revealed that diatoms frontload genes involved in nitrogen assimilation likely in order to outcompete other groups for available nitrogen during upwelling events. We speculate that the evolutionary success of diatoms may be due, in part, to this proactive response to frequently encountered changes in their environment.

Iron storage capacities and associated ferritin gene expression among marine diatoms - Natalie R. Cohen; Elizabeth Mann; Brooke Stemple; Carly M. Moreno; Sara Rauschenberg; Jeremy E. Jacquot; William G. Sunda; Benjamin S. Twining; Adrian Marchetti (Limnology and Oceanography, 2018)
In large regions of the ocean, low iron availability regulates diatom growth and species composition. Diatom species often vary in their physiological response to iron enrichment, with natural and artificial iron additions in iron‐limited regions of the ocean resulting in large blooms of primarily pennate diatoms. The ability of pennate diatoms to proliferate following pulse iron additions has been partly attributed to their ability to acquire and store excess intracellular iron in the iron storage protein ferritin. Recent transcriptome sequencing of diatoms indicate that some centric diatoms also possess ferritin. Using a combination of physiological and molecular techniques, we examined the iron storage capacities and associated ferritin gene expression in phylogenetically diverse centric and pennate diatoms grown under high and low iron concentrations. There were no systematic differences among ferritin‐containing and non‐containing diatom lineages in their ability to store iron in excess of that needed to support maximum growth rates. An exception, however, was the ferritin‐containing pennate diatom Pseudo‐nitzschia granii , native to iron‐limited waters of the Northeast Pacific Ocean. This species exhibited an exceptionally large luxury iron storage capacity and increased ferritin gene expression at high iron concentrations, supporting a role in long‐term iron storage. By contrast, two other diatoms species that exhibited minimal iron storage capacities contained two distinct ferritin genes where one ferritin gene increased in expression under iron limitation while the second showed no variation with cellular iron status. We conclude that ferritin may serve multiple functional roles that are independent of diatom phylogeny.

Corrigendum: Diatom Transcriptional and Physiological Responses to Changes in Iron Bioavailability across Ocean Provinces - Natalie R. Cohen; Kelsey A. Ellis; Robert H. Lampe; Heather McNair; Benjamin S. Twining; Maria T. Maldonado; Mark A. Brzezinski; Fedor I. Kuzminov; Kimberlee Thamatrakoln; Claire P. Till; Kenneth W. Bruland; William G. Sunda; et al. (Frontiers in Marine Science, 2018)

Diatom Transcriptional and Physiological Responses to Changes in Iron Bioavailability across Ocean Provinces - Natalie R. Cohen; Kelsey A. Ellis; Robert H. Lampe; Heather McNair; Benjamin S. Twining; Maria T. Maldonado; Mark A. Brzezinski; Fedor I. Kuzminov; Kimberlee Thamatrakoln; Claire P. Till; Kenneth W. Bruland; William G. Sunda; et al. (Frontiers in Marine Science, 2017)
Changes in iron (Fe) bioavailability influence diatom physiology and community composition, and thus have a profound impact on primary productivity and ecosystem dynamics. Iron limitation of diatom growth rates has been demonstrated in both oceanic and coastal waters of the Northeast Pacific Ocean and is predicted to become more pervasive in future oceans. However, it is unclear how the strategies utilized by phytoplankton to cope with low Fe bioavailability and resupply differ across these ocean provinces. We investigated the response of diatom communities to variable Fe conditions through incubation experiments performed in the Fe mosaic of the California Upwelling Zone and along a natural Fe gradient in the Northeast Pacific Ocean. Through coupling gene expression of two dominant diatom taxa ( Pseudo-nitzschia and Thalassiosira ) with biological rate process measurements, we provide an in-depth examination of the physiological and molecular responses associated with varying Fe status. Following Fe enrichment, oceanic diatoms showed distinct differential expression of gene products involved in nitrogen assimilation, photosynthetic carbon fixation, and vitamin production compared to diatoms from low-Fe coastal sites, possibly driven by the chronic nature of Fe stress at the oceanic site. Genes of interest involved in Fe and N metabolism additionally exhibited divergent expression patterns between the two diatom taxa investigated, demonstrating that diverse diatoms may invoke alternative strategies when dealing with identical changes in their environment. We report here several mechanisms used distinctly by coastal or oceanic diatom communities as well as numerous taxa-specific strategies for coping with Fe stress and rearranging nutrient metabolism following Fe enrichment.

Elevated trace metal content of prokaryotic communities associated with marine oxygen deficient zones - Daniel C. Ohnemus; Sara Rauschenberg; Gregory A. Cutter; Jessica N. Fitzsimmons; Robert M. Sherrell; Benjamin S. Twining (Limnology and Oceanography, 2017)
Little is known about the trace metal content of marine prokaryotes, in part due to their co‐occurrence with more abundant particulate phases in the upper ocean, such as phytoplankton and biogenic detritus, lithogenic minerals, and authigenic Mn and Fe oxyhydroxides. We attempt to isolate these biomass signals in particulate data from the US GEOTRACES Eastern Pacific Zonal Transect (cruise GP16) in the Eastern Tropical South Pacific (ETSP), which exhibited consistent maxima in P and other bioactive trace metals, and minima in particulate Mn, in the oxygen deficient zones (ODZs) of 13 stations. Nitrite maxima and nitrate deficits indicated the presence of denitrifying prokaryotic biomass within ETSP ODZs, and deep secondary fluorescence maxima at the upper ODZ boundaries of 10 stations also suggested the presence of low‐light, autotrophic communities. ODZs were observed as far west as 99°W, more than 2300 km from the South American coast, where eolian lithogenic and lateral/resuspended sedimentary inputs were negligible, presenting a unique opportunity to examine prokaryotic metal stoichiometries. ODZ particulate P maxima can rival gyre mixed layer biomass concentrations, are highly sensitive to oxygen, and are in excess of amounts scavengable by local Fe oxyhydroxides and acid–volatile sulfides. Even after correction for lithogenic and ferruginous–scavenged metals, ODZ P‐maxima are often enriched in Cd, Co, Cu, Ni, V, and Zn, exhibiting particulate trace metal ratios to P that exceed mixed layer biomass ratios by factors of 2–9. ODZ prokaryotic communities may be largely hidden, TM–rich pools involved in the marine cycles of these bioactive trace metals.

The regeneration of highly bioavailable iron by meso‐ and microzooplankton - Jochen Nuester; Steve Shema; Alexander Vermont; David M. Fields; Benjamin S. Twining (Limnology and Oceanography, 2014)
The micronutrient iron (Fe) is rapidly cycled in surface waters, and regenerated Fe supports much of the phytoplankton growth in open ocean waters. Meso‐ and microzooplankton grazing are both important mechanisms to regenerate Fe, but the chemical conditions in the respective digestive systems are different and might affect the bioavailability of Fe. We conducted radiotracer grazing experiments with the copepod Acartia tonsa or the heterotrophic dinoflagellate Oxyrrhis marina feeding on the diatom Thalassiosira pseudonana or the coccolithophore Emiliania huxleyi . Uptake of regenerated 55 Fe by a separate T. pseudonana culture was compared to the uptake of inorganic Fe. Iron regenerated by A. tonsa was taken up 4‐ to 7‐fold faster than inorganic iron. In contrast, no difference was detected between the uptake rate of inorganic Fe and Fe regenerated by O. marina . Ingestion of different prey by A. tonsa revealed that Fe released during diatom digestion was taken up 1.8‐fold faster than Fe released from coccolithophore digestion. Digestive systems and the chemical makeup of the ingested prey are crucial in determining the bioavailability of regenerated Fe. Differences in pH and oxygen saturation between digestive vacuoles and guts may affect the speciation of regenerated Fe, and the release of ferrous Fe might contribute to the bioavailability of regenerated Fe. The ecological structure determines the importance of regenerated Fe for a particular ecosystem.

Differential remineralization of major and trace elements in sinking diatoms - Benjamin S. Twining; Scott D. Nodder; Andrew L. King; David A. Hutchins; Gary R. LeCleir; Jennifer M. DeBruyn; Elizabeth W. Maas; Stefan Vogt; Steven W. Wilhelm; Philip W. Boyd (Limnology and Oceanography, 2014)
Macronutrients in sinking phytoplankton are typically remineralized at different rates, but less is known about the fate of micronutrient metals associated with sinking cells. Scavenging, the presence of co‐occurring abiotic particles, and inadvertent contamination limit the utility of bulk analytical approaches to study remineralization of trace metals in sinking phytoplankton. We used synchrotron x‐ray fluorescence mapping to measure macronutrients (P, S, and Si) and trace metals (Fe, Ni, and Zn) in individual cells of the diatom Asterionellopsis glacialis during a spring bloom in subtropical waters off New Zealand. P, S, Zn, and Ni were released significantly faster than Fe and Si from sinking cells in the upper 200 m. Bulk particulate element fluxes to sediment traps indicated similar trends, but biogenic silica flux was attenuated much faster than Si was lost from intact sinking cells collected in the traps. The metals were spatially co‐located with P and S in upper ocean cells, but this association with P and S (based on a spatial resolution of 450 nm) was largely absent in sinking cells. In contrast, Fe retained a weak spatial association with Si, suggesting that remineralized Fe may be re‐scavenged onto cell surfaces. As a result, dissolved Fe : macronutrient stoichiometries in the water column likely underestimate stoichiometries in sinking cells. We propose linkages between the selective loss of diatom cellular components (e.g., ribosomes or phospholipid membranes, Zn‐finger proteins, and urease) and the observed recycling of specific elements (P, Zn, and Ni, respectively), which set the stoichiometry of macro‐ and micronutrient supply to surface waters.

Microscale patchiness leads to large and important intraspecific internal nutrient heterogeneity in phytoplankton - Vanni Bucci; Daliangelis Nunez-Milland; Benjamin S. Twining; Ferdi L. Hellweger (Aquatic Ecology, 2012)

Variations in Synechococcus cell quotas of phosphorus, sulfur, manganese, iron, nickel, and zinc within mesoscale eddies in the Sargasso Sea - Benjamin S. Twining; Daliangelis Nuñez-Milland; Stefan Vogt; Rodney S. Johnson; Peter N. Sedwick (Limnology and Oceanography, 2010)
The quotas of P, S, Mn, Fe, Ni, and Zn in individual Synechococcus cells collected from the surface and deep chlorophyll maximum (DCM) layer of three mesoscale eddies in the Sargasso Sea were measured using synchrotron X‐ray fluorescence microscopy. Cells in a mode‐water eddy had significantly higher P (57 ± 10 amol) and Mn (28 ± 7 zmol) cell quotas than cells collected from a cyclone (22 ±2 amol and 10 ± 1 zmol, respectively) or anticyclone (25 ± 3 amol and 18 ± 3 zmol, respectively). Conversely, Ni and Zn quotas were significantly higher in the cells from the anticyclone (92 ± 19 and 561 ± 150 zmol, respectively) than in cells from the cyclonic (25 ± 4 and 35 ± 7 zmol, respectively) or mode‐water (30 ± 9 and 21 ± 8 zmol, respectively) eddies. These changes may reflect biochemical responses (e.g., production of urease and alkaline phosphatase) to gradients in inorganic N and P supplies. Cellular quotas of Fe (111 ± 17 zmol in the cyclone) and S (52 ± 6 amol in the cyclone) did not vary significantly among eddies despite two‐ to threefold higher dissolved and particulate Fe concentrations in the anticylone. Cells collected from 10‐m depth contained approximately 80% more Ni and S than cells collected from the DCM, potentially reflecting cell responses to heightened oxidative stress. Depthrelated trends varied by eddy for the other elements. Cellular P and Zn varied significantly during repeated samplings of the cyclone, with quotas of both elements dropping as bulk chlorophyll biomass in the DCM increased. These data demonstrate the dynamic responses of phytoplankton elemental composition to physical and chemical environmental gradients.

Potential role of copper availability in nitrous oxide accumulation in a temperate lake - Benjamin S. Twining; Steven E. Mylon; Gaboury Benoit (Limnology and Oceanography, 2007)
Denitrifying bacteria require copper for the synthesis of nitrous oxide reductase. In the absence of sufficient bioavailable Cu, nitrous oxide (N 2 O) may accumulate in natural waters during denitrification. Cultures of Paracoccus denitrificans and natural bacterial assemblages collected from a mesotrophic lake (Linsley Pond) were grown at varying Cu concentrations to determine the Cu speciation that results in elevated N 2 O accumulation. P. denitrificans experienced Cu limitation beginning at inorganic Cu concentrations of 0.6 fmol L −1 (−log of inorganic Cu, pCu′, = 15.2). The natural community did not show an effect until pCu′ was reduced to 23.7 with 8‐hydroxyquinoline, resulting in an approximate 10‐fold increase in N 2 O concentrations during denitrification. Additions of ethylenediaminetetraacetic acid alone to natural communities did not affect N 2 O concentrations. Natural copper‐binding ligands detected with competitive ligand exchange‐cathodic stripping voltammetry occurred at concentrations of 6 to 25 nmol L21 with conditional stability constants (K Cu 2 + L ) between 10 14.4 and 10 15.1 . Although more than 99% of total Cu in Linsley Pond was bound to these ligands, inorganic Cu concentrations remained 10 orders of magnitude above those found to increase N 2 O accumulation during denitrification incubations. Measurements of nitrogen species, dissolved oxygen, and sulfide in the water column of Linsley Pond over the spring growing season revealed that N 2 O was produced by assimilatory nitrate reduction and nitrification in addition to denitrification, with nitrification generating most of the N 2 O found in the surface waters of the lake. The results suggest that inorganic Cu concentrations in Linsley Pond are sufficient to support denitrification. Moreover, some denitrifying bacteria may be able to access organically bound Cu, reducing the potential for this metal to affect N 2 O production in other aquatic environments.

Element stoichiometries of individual plankton cells collected during the Southern Ocean Iron Experiment (SOFeX) - Benjamin S. Twining; Stephen B. Baines; Nicholas S. Fisher (Limnology and Oceanography, 2004)
During the Southern Ocean Iron Experiment (SOFeX), we analyzed Si, P, S, Mn, Ni, and Zn in individual diatoms, autotrophic flagellates, and heterotrophic flagellates with synchrotron‐based X‐ray fluorescence (SXRF) and calculated cellular C from measurements of cell size. Element stoichiometries for the different types of protists (normalized to either C, S, or P) were generally in good agreement with prior bulk analyses of natural assemblages but also revealed previously undocumented differences in elemental composition among cell types. Flagellated cells contained 39% more P than diatoms, which in turn contained 79% more Mn, 3‐fold more Ni, and 2.6‐fold more Zn than flagellates. Heterotroph cells contained approximately 40% more P and twice as much Zn as autotrophs. Manganese and Ni stoichiometries were negatively related to cell volume, while larger cells contained more Zn per mole C. Iron fertilization resulted in an approximate doubling of Mn, Ni, and Zn quotas and smaller increases in cellular P, but the timing of the stoichiometric changes varied between the two patches. Silicon contents of diatoms dropped approximately 40% after the first Fe addition but returned to prefertilization levels as cellular P doubled following the second addition, resulting in 40% lower Si : P ratios in the fertilized waters. The mean elemental stoichiometries calculated for all cells analyzed were comparable with previously published extended Redfield ratios for mixed plankton assemblages, but the observed differences between diatoms and flagellates and between autotrophs and heterotrophs indicate that valuable information is lost when all types of co‐occurring plankton are grouped together for analysis.

Trophic transfer of trace metals from protozoa to mesozooplankton - Benjamin S. Twining; Nicholas S. Fisher (Limnology and Oceanography, 2004)
Radiotracer techniques were used to quantify the assimilation and subsequent efflux of silver, cadmium, iron, mercury, thallium, and zinc by mesozooplankton fed ciliates, heterotrophic dinoflagellates, or heterotrophic flagellates, and the results were compared with published values measured for phytoplankton prey. The subcellular distribution of the metals within the prey cells was also determined and related to their bioavailability. Marine copepods assimilated 59ߚ82% of Ag, 83ߚ92% of Cd, 32ߚ66– of Fe, 14ߚ49% of Hg, and 71ߚ78% of Zn ingested with protozoan prey. Higher Ag, Cd, Fe, and Hg assimilation efficiencies were observed for at least one of the species of protozoa than reported in the literature for phytoplankton. Significant differences in assimilation were not observed for Zn or for Tl fed to freshwater Ceriodaphnia in either protozoa or phytoplankton. The higher assimilation efficiencies of protozoan metals, when observed, were matched by higher fractions of metals in the cytoplasm of protozoa. A biokinetic model used to calculate steadyߚstate metal concentrations in copepods indicates that copepods may contain 119% more Ag and 44% more Zn when feeding on ciliates instead of diatoms, possibly resulting in sublethal toxic effects at Ag and Zn concentrations reported for the Hudson River estuary. Further, higher assimilation and efflux rates of protozoan Fe may enhance remineralization of this limiting nutrient by mesozooplankton in high nutrient, low chlorophyll regions.

Assimilation of micro‐ and mesozooplankton by zebra mussels: A demonstration of thefood web link between zooplankton and benthic suspension feeders - Wai Hing Wong; Jeffrey S. Levinton; Benjamin S. Twining; Nicholas Fisher (Limnology and Oceanography, 2003)
We tested the hypothesis that rotifer species in the micro‐ and mesozooplankton are a potential food source for zebra mussels. We labeled phytoplankton with 14 C, fed them to two species of rotifers (140–210 µm length) that were previously found abundantly in the Hudson River and had declined following a zebra mussel invasion, and estimated the assimilation of carbon. Assimilation efficiencies were found to be ~37.47–54.0%. Combined with our feeding experiments, the data on rotifer densities before and after the invasion allowed us to calculate the energy budgets for zebra mussels. Before zebra mussels dominated the Hudson River in 1992, the absorption of energy from rotifers was about two to three times higher than that necessary to maintain its routine metabolic rate and contributed about 0.349–0.662 J h −1 to mussel growth and reproduction, conferring a positive scope for growth. Since the zebra mussels became abundant in the Hudson River, assimilation of rotifers is still sufficient to explain ~16.4–23.1% of the mussels' routine metabolic rate. Therefore, rotifers play a conceivably large role in the energy budget of zebra mussels, whether at high rotifer concentrations (before the invasion) or at low rotifer concentrations (after the invasion). This is the first quantitative evidence for a trophic link between benthic bivalve mollusks and larger micro‐ and mesozooplankton that might extend to marine systems where bivalves can derive nutrition from microzooplankton, including planktonic invertebrate larvae. Combined with other recent results, this study documents a benthos‐zooplankton trophic loop, demonstrating potentially strong top‐down control by dense bivalves on aquatic systems.

Evidence of homing behavior in the coral reef mysid Mysidium gracile - Benjamin S. Twining; John J. Gilbert; Nicholas S. Fisher (Limnology and Oceanography, 2000)
Mysid swarms at benthic coral reef sites disperse into the water column in the evening and reform at the exact same location the following morning, possibly reflecting homing behavior of individual mysids. To facilitate tracking of individual mysids, we radiolabeled part of a swarm of Mysidium gracile with the gamma‐emitting radioisotope 65 Zn and released the labeled animals back to the focal swarm on a reef in Discovery Bay, Jamaica. We collected the focal swarm and surrounding swarms the next morning to determine the location of the labeled individuals following nighttime dispersal. Seventy‐seven percent of the radiolabeled mysids returned to the same site the next day, and 13% of the labeled individuals were recovered from other nearby swarms. This recovery rate cannot be attributed to random reaggregation and suggests that mysids use a homing behavior to facilitate swarm reformation. This is the first unequivocal evidence of homing behavior in demersal zooplankton.